Antičny topos «vladyčestva nad Aziej» i koncepcija nepreryvnoj nadregional’noj gosudarstvennosti na bližnem i srednem vostoke v I tys. do n. ė. - Ladynin, I.A.
Resümee: Classical Topos of ‚The Kingship of Asia’ and the Concept of Continuous Multiregional Monarchy in the Near and Middle East, First Millennium B.C.